Pectate lyase is a factor in the adaptability for Heterodera glycines infecting tobacco - Zhong-ling TIAN; Hong-li SHI; Munawar Maria; Jing-wu ZHENG (Journal of Integrative Agriculture, 2019)
The soybean cyst nematode, Heterodeara glycines, is a serious pathogen of soybean, and reported to be the host of a wide range of Fabaceae. In the present study, the host specificity and reproductivity of two populations of H. glycines collected from soybean and tobacco were identified and characterized. The comparative identity between β-1,4-endoglucanase, pectate lyase and chorismate mutase of H. glycines parasitizing on soybean and tobacco were 99, 97 and 98%, respectively. The qRT-PCR analysis indicated that the expression of pectate lyase 2 gene was significantly higher in second-stage juveniles of H. glycines Henan population parasitizing on tobacco than that of H. glycines Shanxi population parasitizing on soybean. In addition, the pectic acid content of cell wall was significantly higher (45%) in the roots of tobacco than the roots of soybean. Our results indicate that the changes in transcript parasitism genes may be a result of long-term evolution illustrating how a plant-parasitic nematode adapts to the host environment for optimal infestation and survival.